2020
DOI: 10.5093/clysa2020a8
|View full text |Cite
|
Sign up to set email alerts
|

Burnout in Mental Health Professionals: The Roles of Psychological Flexibility, Awareness, Courage, and Love

Abstract: The burntout phenomenon has been well-studied in psychology and is receiving increasing attention from contextual-behavioral approaches. In the dominant model of burnout, which has garnered much empirical support (Maslach et al., 2001), burnout comprises three dimensions: emotional exhaustion (EE; being emotionally overextended and depleted), depersonalization (D; feeling negative, callous, and excessively detached from clients and customers), and lack of personal accomplishment (PA; feeling incompetent and la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Different studies have found strong associations between psychological flexibility and the burnout syndrome (Losa Iglesias et al, 2010;Noone & Hastings, 2011). These correlations have also been described in the case of health professionals, whose constant exposure to human suffering may trigger emotional exhaustion through the usage of experiential avoidance (Ortiz-Fune et al, 2020).…”
Section: Introductionmentioning
confidence: 81%
“…Different studies have found strong associations between psychological flexibility and the burnout syndrome (Losa Iglesias et al, 2010;Noone & Hastings, 2011). These correlations have also been described in the case of health professionals, whose constant exposure to human suffering may trigger emotional exhaustion through the usage of experiential avoidance (Ortiz-Fune et al, 2020).…”
Section: Introductionmentioning
confidence: 81%
“…In another study that focused on self-efficacy change as the mediator on the relationship between exhaustion and disengagement among 346 MHP, Rogala et al [ 20 ] reported that exhaustion predicted disengagement about 6 months later and that self-efficacy beliefs have a mediating effect on the relationship. In addition to self-efficacy, other variables such as mindfulness and psychological flexibility can also mediate the relationship between exhaustion and disengagement [ 21 , 22 ]. More research is warranted in this area to help us better understand the inter-relationships between germane factors and identify strategies to reduce burnout.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, psychological flexibility may act as a protective role of burnout and this relationship has been found in several studies in various work contexts. These studies showed that psychological flexibility negatively relates to burnout ( Lloyd et al, 2013 ; Noone & Hastings, 2011 ; Ortiz-Fune et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%